Establishment and practice of biosystems engineering discipline - CHEN Su-shan (浙江大学学报. 农业与生命科学版)
As the first biosystems engineering discipline in China, The Biosystems Engineering Discipline is a new one which established by innovation of agricultural engineering discipline and broadening the research field of agricultural engineering discipline. Based on the theory and practice, This paper explored on the background and base of the innovation, the training objectives and pattern of new discipline's talent, the established measure and mechanism of the new discipline and so on.